2022
DOI: 10.1038/s41388-022-02578-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the 5′UTR landscape reveals isoform switches to drive translational efficiencies in cancer

Abstract: Transcriptional and translational control are key determinants of gene expression, however, to what extent these two processes can be collectively coordinated is still poorly understood. Here, we use Nanopore long-read sequencing and cap analysis of gene expression (CAGE-seq) to document the landscape of 5′ and 3′ untranslated region (UTR) isoforms and transcription start sites of epidermal stem cells, wild-type keratinocytes and squamous cell carcinomas. Focusing on squamous cell carcinomas, we show that a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
(80 reference statements)
0
24
0
Order By: Relevance
“…Cumulative evidence from genome-wide analyses and bioinformatic predictions indicate that thousands of genes may undergo ATI events from both in-frame AUG and near-cognate start codons. This enriches the diversity of the cellular proteome by producing extended or truncated protein isoforms, with the potential gain or loss of functional domains in physiological and pathological situations [49][50][51][52][53][54][55][56][57] . Given this complexity, genetic approaches mutating the main start codons to understand the function of specific protein isoforms must consider the potential contribution of ATI events to the protein pool.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidence from genome-wide analyses and bioinformatic predictions indicate that thousands of genes may undergo ATI events from both in-frame AUG and near-cognate start codons. This enriches the diversity of the cellular proteome by producing extended or truncated protein isoforms, with the potential gain or loss of functional domains in physiological and pathological situations [49][50][51][52][53][54][55][56][57] . Given this complexity, genetic approaches mutating the main start codons to understand the function of specific protein isoforms must consider the potential contribution of ATI events to the protein pool.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the number of mRNAs whose TE is estimated in a typical experiment is ∼ 20 ′ 000, which corresponds roughly to one isoform per gene. Accurate estimation of the TE of individual isoforms could be an important direction of methodological development [35, 36]. However, it is unlikely that many isoforms are simultaneously expressed at a high enough level to be accurately measured in a given cell type, or that sufficiently accurate data can be currently obtained from single cells [37] that express distinct isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, zebrafish switching 5′ UTR variants can display different motif grammar, and DaniO5P indicates that changes to motif composition impacts their translational effect. Interestingly, cancer cells take advantage of TSS switches to expose or mask motifs to promote translation of a cohort of growth-promoting transcripts (Weber et al , 2023). Moreover, two studies have reported 5′ UTR isoform-specific translation by binding of an RBP to one of the 5′ UTR isoforms but not the other (Aeschimann et al , 2017; Popovitchenko et al , 2020).…”
Section: Discussionmentioning
confidence: 99%